Comparative Anatomy of Mitral and Tricuspid Valve: What Can the Interventionlist Learn From the Surgeon - Pozzoli, Alberto; Zuber, Michel; Reisman, Mark; Maisano, Francesco; Taramasso, Maurizio (Frontiers in Cardiovascular Medicine, 2018)
Transcatheter valve interventions on the mitral and tricuspid valves entail increasing complexity. Part of the knowledge that has been generated during the development of mitral devices can be transferred to the tricuspid valve (TV). However, a deeper understanding of the peculiar anatomy of the TV and of the right heart chambers, together with differences and similarities between the two valves, is fundamental. This report compares the anatomy of the mitral and tricuspid valves, and its inferences with regard to transcatheter treatments. Condensed abstract This report explores anatomical similarities and differences between the mitral and the tricuspid valves, and their implications with regard to transcatheter treatments.